The hidden curriculum of a special education program in a Junior Science College in Malaysia - S. I., Fatimah; Roslan, Samsilah; Alwi, Nor Hayati; Ghiami, Zeinab; Suandi, Turiman; Hamzah, Azimi (Medwell Journals, 2016)
The purpose of this study was to explore the facets of the hidden curriculum in a Junior Science College from the perspective of students labelled as gifted. This college is set up specifically for gifted and high academic achiever students. A qualitative approach was chosen to gather the data from former students and current teachers of this college. The data was collected from three focus group interviews with 16 former students, individual interviews with four students and 6 teachers, observations of school activities and document reviews. The data was analysed manually, codes and categories were identified and a rich description based on the categories was written to answer the research question. The results showed that the hidden curriculum is the result of the practices, procedures, rules, relationships, structures and physical characteristics of the Special Education Program (SEP). Eight themes were identified which resulted in the learning of intrapersonal and interpersonal skills. The study concluded that the hidden curriculum facilitated the transmission of social norms while the learning improved positive interpersonal and intrapersonal skills in the students, in spite of the restrictive nature of the special education program. According to the results, it can be concluded that flexibility and creativity in instruction promotes positive traits in students and teachers.